Association of autophagy status with amount of Fusobacterium nucleatum in colorectal cancer. Issue 4 (3rd February 2020) - Haruki, Koichiro; Kosumi, Keisuke; Hamada, Tsuyoshi; Twombly, Tyler S; Väyrynen, Juha P; Kim, Sun A; Masugi, Yohei; Qian, Zhi Rong; Mima, Kosuke; Baba, Yoshifumi; da Silva, Annacarolina; Borowsky, Jennifer; et al.
Abstract: Fusobacterium nucleatum ( F. nucleatum ), which has been associated with colorectal carcinogenesis, can impair anti‐tumour immunity, and actively invade colon epithelial cells. Considering the critical role of autophagy in host defence against microorganisms, we hypothesised that autophagic activity of tumour cells might influence the amount of F. nucleatum in colorectal cancer tissue. Using 724 rectal and colon cancer cases within the Nurses' Health Study and the Health Professionals Follow‐up Study, we evaluated autophagic activity of tumour cells by immunohistochemical analyses of BECN1 (beclin 1), MAP1LC3 (LC3), and SQSTM1 (p62) expression. We measured the amount of F. nucleatum DNA in tumour tissue by quantitative polymerase chain reaction (PCR). We conducted multivariable ordinal logistic regression analyses to examine the association of tumour BECN1, MAP1LC3, and SQSTM1 expression with the amount of F. nucleatum, adjusting for potential confounders, including microsatellite instability status; CpG island methylator phenotype; long‐interspersed nucleotide element‐1 methylation; and KRAS, BRAF, and PIK3CA mutations. Compared with BECN1‐low cases, BECN1‐intermediate and BECN1‐high cases were associated with lower amounts of F. nucleatum with odds ratios (for a unit increase in three ordinal categories of the amount of F. nucleatum ) of 0.54 (95% confidence interval, 0.29–0.99) and 0.31 (95% confidence interval, 0.16–0.60), respectively ( P trend  < 0.001 across ordinal BECN1 categories) . Tumour MAP1LC3 and SQSTM1 levels were not significantly associated with the amount of F. nucleatum ( P trend  > 0.06). Tumour BECN1, MAP1LC3, and SQSTM1 levels were not significantly associated with patient survival ( P trend  > 0.10). In conclusion, tumour BECN1 expression is inversely associated with the amount of F. nucleatum in colorectal cancer tissue, suggesting a possible role of autophagy in the elimination of invasive microorganisms. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.